ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN BERMUATAN MITIGASI BENCANA GEMPA BUMI DI SD - Sari, Sanita; Mulyadiprana, Ahmad; Mohamad Setiadi, Pidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesia is ranked as the third most disaster-prone country according to the World Risk Report 2022. One of the most frequent disasters is earthquakes, with children among the most vulnerable groups. However, studies show that elementary school students have limited knowledge and preparedness regarding earthquake mitigation. This study aims to identify the need for effective learning media to support earthquake disaster mitigation education in elementary schools. The research employed a qualitative descriptive method. Data were collected through interviews with a fifth-grade teacher, direct observation of the school environment, and document analysis of teaching materials. The findings reveal that the current curriculum and textbooks do not explicitly present earthquake mitigation content. Furthermore, although the classroom environment is conducive to learning, essential disaster safety infrastructure, such as evacuation route signs, is still lacking. The teacher stated that students respond better to visual media, especially picture-based and contextually relevant materials. Based on these findings, the study concludes that there is a significant need for learning media that are engaging, concrete, and suited to students’ cognitive development stages. Picture storybooks are recommended as an effective medium, as they combine narrative and visual elements, making abstract concepts like disaster mitigation more comprehensible to young learners. The results support the integration of disaster education through appropriate media to enhance student preparedness in earthquake-prone regions.